Optimized daily diet composition for a nutritionally balanced diet: An application of Fuzzy Multiple Objective Linear Programming - Tom, Mary; Wibovo, Santoso; Williams, Susan (2016 IEEE International Conference on Fuzzy Systems (FUZZ-IEEE), 2016)
Nutrition related diseases such as Cardiovascular Diseases, type 2 diabetes, and certain types of cancers are widely prevalent, and increasing in both developed and developing countries. This escalates the need to consistently follow a nutritionally balanced diet. Formulation of nutritionally balanced Meals is a complex task, which requires considerable effort, time, and intellectual capability for evaluation of Menu items and analysis of a range of nutrient values. As a step towards automating this task, this interdisciplinary study presents a fuzzy optimization model applying Fuzzy Multi-objective Linear Programming (FMOLP) to compose a daily diet consisting of nutritionally balanced Meals which limit nutrients such as cholesterol, sugar, saturated fat, and sodium. An effective algorithm is developed to create a pare to optimal solution set of optimized daily diet choices. The model is tested using one hundred Menu items, for demonstrating the applicability of the model in composing a nutritionally balanced diet.